Router Resource Management Research - Cincikas, G.; Japertas, S. (Elektronika ir Elektrotechnika, 2012)
The problem of resource management of the network node is analysed in the paper. It is offered to apply the L. Walras dynamic model for the solution of this problem. The stability of the resource management of network node in the cases of content and variable delay is investigated. It is expected that having applied the offered model of the system resource management, the system will be capable to change its state smoothly without reaching the critical one. Ill. 3, bibl. 7 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1825